PENGARUH PENGGUNAAN LIMBAH BETON SEBAGAI SUBSTITUSI AGREGAT KASAR PADA CAMPURAN BETON 10%, 20%, 30% TERHADAP KUAT TEKAN BETON FC’ 20,75 MPA - Bobi Saputra; Ishak Ishak; Selpa Dewi (Ensiklopedia Research and Community Service Review, 2021)
The development of an increasingly advanced era of globalization has led to the development of construction technology that is increasingly rapid. construction waste in the form of reinforcing steel, wood and concrete has a negative impact on the environment around the construction project. One example of efforts to reduce the impact of this waste is to reuse concrete waste for the use of new concrete. This study aims to determine how much influence the use of concrete waste as a substitute for coarse aggregate on the value of the compressive strength of concrete, and determine the compressive strength of the substitution of coarse aggregate with 10%, 20% and 30% concrete waste in the concrete mixture. The method used in this research is experimental research in which to obtain data and research results by conducting tests and research in the laboratory. the results of concrete experiments that have been carried out and the data obtained with the quality of normal concrete fc 20.75 Mpa and concrete with the substitution of waste concrete against coarse aggregate can cause a decrease in the compressive strength of concrete against normal concrete. The higher the percentage of concrete waste mixture in concrete can reduce the quality of its compressive strength, waste concrete is not good for use as a mixture of concrete.  Keywords: Concrete, Waste Concrete, Compressive Strength